2022
DOI: 10.1097/ana.0000000000000883
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events in the Pediatric Cardiac Catheterization Suite: Does Having Pediatric Cardiac Anesthesiologists Make a Difference?

Abstract: will be important to inform how best to provide safe care and allocate resources. Further studies are needed to determine the incidence of AE in the subgroups of very high-risk patients requiring extracorporeal membrane oxygenation support, on ventricular assist devices, and those with recent open-heart surgery.*ASA physical status score cannot be included in the regression analysis in these groups due to small samples (only 1 single procedure with ASA 5 in each group). ASA indicates American Society of Anesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…23 Meta-analysis demonstrating RIP had no effect on prolonged MV or ICU LOS. Huang et al 24 Preop low SpO2, high lactate, and longer MV associated with increased LOS after TAPVR repair Neurodevelopment Simpao et al 25 No association between volatile anesthesia exposure and deleterious neurodevelopmental effects Resource allocation Backer et al 26 Multidisciplinary guidelines and recommendations for congenital heart centers Lin et al 28 Similar adverse event rates for cardiac catheterization procedures with noncardiac trained pediatric anesthesiologists Black et al 29 Similar adverse event rates in the cardiac catheterization lab despite increasing patient complexity Reichl et al 30 Cardiac imaging can be done safely in an ambulatory setting Baijal et al 34 The importance of risk stratification and anesthesiologist level of training in patients with CHD undergoing noncardiac procedures Waldman et al 35…”
Section: Risk Assessment and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Meta-analysis demonstrating RIP had no effect on prolonged MV or ICU LOS. Huang et al 24 Preop low SpO2, high lactate, and longer MV associated with increased LOS after TAPVR repair Neurodevelopment Simpao et al 25 No association between volatile anesthesia exposure and deleterious neurodevelopmental effects Resource allocation Backer et al 26 Multidisciplinary guidelines and recommendations for congenital heart centers Lin et al 28 Similar adverse event rates for cardiac catheterization procedures with noncardiac trained pediatric anesthesiologists Black et al 29 Similar adverse event rates in the cardiac catheterization lab despite increasing patient complexity Reichl et al 30 Cardiac imaging can be done safely in an ambulatory setting Baijal et al 34 The importance of risk stratification and anesthesiologist level of training in patients with CHD undergoing noncardiac procedures Waldman et al 35…”
Section: Risk Assessment and Outcomesmentioning
confidence: 99%
“…26 Other studies investigated whether an anesthesiologist's training level is associated with adverse outcomes in pediatric cardiac patients. Lin et al 28 evaluated 3761 cardiac catheterization procedures from a single-center and found adverse event rates were statistically similar regardless of whether anesthesia was administered by a cardiac or noncardiac anesthesiologist. Furthermore, an article from Pediatric Anesthesia's July issue by Black et al reviewed severe adverse events for patients undergoing catheterization procedures at their single institution.…”
Section: Commentary On Baijal Et Al Highlighting the Decreased Mortal...mentioning
confidence: 99%
“…39 Elsewhere, two retrospective studies found no association between anesthesia training and perioperative complications in children with CHD undergoing non-cardiac surgery or cardiac catheterization, no matter if non-cardiac or cardiactrained pediatric anesthesiologists provided care. 40,41 Abdominal Transplant Katayama et al reviewed an eventful year for abdominal organ transplantation, 42 with record numbers of kidney and liver transplants performed in the United States. 3 But the review article also stressed how donation after cardiac death (DCD) has increased the donor pool for pancreatic transplants.…”
Section: Congenital Heart Diseasementioning
confidence: 99%
“…39 Elsewhere, two retrospective studies found no association between anesthesia training and perioperative complications in children with CHD undergoing non-cardiac surgery or cardiac catheterization, no matter if non-cardiac or cardiac-trained pediatric anesthesiologists provided care. 40,41…”
Section: Congenital Heart Diseasementioning
confidence: 99%